Side-to-Side Differences in Bone Mineral Density, Bone Mineral Content, and Lean Mass in Healthy Subjects - Brance, María Lorena (2025)
Background: Limb dominance is influenced by daily activity and muscle strength. Previous studies have demonstrated lateral differences in bone mineral density (BMD), bone mineral content (BMC), and lean mass as a result of asymmetric mechanical loading. Understanding these variations is crucial, especially in conditions with regional bone demineralization, where the contralateral limb can serve as a reference. We aimed to analyze side-to-side differences in BMD, BMC, and lean mass, as measured by dual energy X-ray absorptiometry (DXA), in healthy subjects.Methods: A cross-sectional study included 802 whole-body composition assessments in Spanish adults (20-80 years). Athletes and individuals with bone metabolism disorders were excluded. Hand and foot dominance were self-reported. BMD, BMC, and lean mass were measured using a DXA scanner (Lunar Prodigy).Results: The sample (57.1% women, 42.9% men; mean age, 53.0±16.7 years) showed strong correlations between dominant and non-dominant limbs (r>0.90). The dominant upper limb had significantly higher BMD (~4%), BMC (~5-6%), and lean mass (~3-4%) in both sexes. In women, the dominant lower limb showed slight differences (~1%), while in men, only lean mass was significantly higher. Aging led to BMD and BMC reductions after a peak in the fourth decade in women and the third in men. Lean mass showed a higher decline in men in both upper and lower limbs.Conclusions: Limb dominance affects body composition differently between sexes, primarily in the upper limb, potentially due to differences in physical activity or mechanical loading. This study provides insight into how laterality and aging influence body composition in healthy individuals.